The classroom, an inadequate mechanism for advancing diversity via religion education in the South African context - McDonald, Zahraa (Journal for the study of religion, 2015)
In the interest of instilling a respect for diversity in learners, the South African policy on religion and education (DoE 2003) aims to recognise religion in teaching and learning in public schools. The policy provides one mechanism for advancing diversity via religion education; Life Orientation in the classroom. Research however suggests that embracing religious diversity in the classroom is challenging. This article therefore examines whether this is an adequate mechanism for achieving the intended outcome of the policy. The article proceeds to examine the mechanism for advancing diversity via religion education, the classroom, in relation to integration of the post-apartheid classroom and teachers' capacity. The article finds that the mechanism to advance diversity via religion education provided by the national policy on religion education is inadequate within the current South African context.